2019
DOI: 10.1016/j.jcf.2018.05.013
|View full text |Cite
|
Sign up to set email alerts
|

AGTR2 absence or antagonism prevents cystic fibrosis pulmonary manifestations

Abstract: These results identify that reduced AGTR2 signaling is beneficial to CF lung function, and suggest the potential of manipulating the angiotensin-signaling pathway for treatment and/or prevention of CF pulmonary disease. Importantly, the beneficial effects were not CF gene mutation dependent, and were able to be reproduced with pharmacologic antagonism. As there are clinically approved drugs available to target the renin-angiotensin signaling system, these findings may be quickly translated to human clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…Their severity probabilities calculated on sex-age (0.9 and 0.94) do not mirror the relatively mild clinical outcome, which is instead better represented by the severity probability calculated in IPGS only (0.23 and 0.41). Those two patients presented ultra-rare variants in ACE2 gene, likely responsible for reduced viral load [35], and in AGTR2 gene, which reduced activity is known to prevent cystic fibrosis pulmonary manifestation [36].…”
Section: Resultsmentioning
confidence: 99%
“…Their severity probabilities calculated on sex-age (0.9 and 0.94) do not mirror the relatively mild clinical outcome, which is instead better represented by the severity probability calculated in IPGS only (0.23 and 0.41). Those two patients presented ultra-rare variants in ACE2 gene, likely responsible for reduced viral load [35], and in AGTR2 gene, which reduced activity is known to prevent cystic fibrosis pulmonary manifestation [36].…”
Section: Resultsmentioning
confidence: 99%
“…Gene modifier studies in CF have identified some therapeutic targets. 101 To date no clinical interventions have resulted, however, early trials are underway, which will hopefully result in efficacious new treatments. 101 Another potential application of identifying gene modifiers, that has not been the primary aim, but perhaps represents a missed opportunity, is using them to stratify patients into different risk categories (i.e mild lung disease, severe lung disease).…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that the expression of AGTR2mRNA is less in kidney tissue and the highest in lung tissue, which is tissue-specific. And in 2015 the GWAS study confirmed that the variation of the locus containing AGTR2 on the X chromosome was significantly associated with lung function in patients with cystic fibrosis [28] .In vitro, studies have demonstrated that the deficiency of the AGTR2 gene can normalize the pulmonary function index of mice with cystic pulmonary fibrosis [29] . Overexpression of the AGTR2 receptor can increase pulmonary vascular permeability and worsen pulmonary inflammation in mice with LPS-induced acute lung injury [30] .…”
Section: Fig 6 Schematic Diagram Of Lung Injury Model Mediated By Comentioning
confidence: 98%